STRATEGI KELANGSUNGAN HIDUP GELANDANGAN-PENGEMIS (GEPENG) - Maghfur Ahmad (IAIN Pekalongan, 2010)
This research reveals many factors that cause someone become a vagrant-beggar; activity meaning of vagrant-beggars; and the strategies that are done by them to survive in Pekalongan City. Phenomenology was used to analyze that. The data were investigated through in-depth interview and observation. The result of this research reveals that the vagrant-beggars do begging activities because of economic, far advanced in life, physical defect, and minimum vacancy factors. To them, knocking around and begging activities have a meaning as a protest movement, a profession, a mean to purify and grow the have’s property and avoid the have from bad luck, and a noble deed compared with stealing. Beside that, to be able to survive, they improve many strategies to be able to compete for their viability